Trainee Trait Empathy, Age, Trainer Functioning, Client Age and Training Time as Discriminators of Successful Empathy Training - Steibe, Susan C.; Boulet, Donald B.; Lee, Daniel C. (Canadian Journal of Counselling and Psychotherapy, 2012)
The state-trait model (Spielberger, Gorsuch, & Lushene, 1969) was applied to empathy training. Empathy training was seen as resulting in a change in trainees' state empathy level. It was hypothesized that trainees' state empathy level would be a function of trait empathy level, age of trainee, trainee's perception of the trainer, age of client, order of presentation of measures, and training time. Sixty-two religious women who were non-professional counsellors were given either 6 or 12 hours of systematic empathy training. State empathy level was measured from a thirty-minute standard interview. From tape recordings of the Helping Interview, groups were formed on the basis of state empathy level and amount of training time. The data were analyzed by two-group and four-group discriminant analyses. Significant discriminating patterns were found for successful vs. unsuccessful trainees in both 12 and 6 hour training groups. Successful trainees were most easily differentiated and predicted on the basis of young age, high level of trait empathy, and high perception of the empathie functioning of the trainer. Implications for short-term training programs and for further research were discussed.